The Effect of Chromium Coating Thickness on ST37 Material on Corrosion Rate Using the Linear Polarization Resistance (LPR) Technique - Jovano Cilion Athallah; Firman Yasa Utama (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
ST37 low-carbon steel is widely used in construction and decorative applications such as house window grilles due to its good mechanical properties, ease of fabrication, and cost-effectiveness. However, this material has a major drawback in the form of low corrosion resistance, especially in open environments that are humid and contain chloride ions. One effort to improve the corrosion resistance of ST37 steel is through the chromium electroplating process. This study aims to analyze the effect of variations in chromium plating time on coating thickness and the corrosion rate of ST37 steel. The electroplating process was carried out using a chromium-based electrolyte solution with a constant voltage of 12 volts and plating time variations of 25, 35, and 45 minutes. The coating thickness was measured using a thickness gauge, while the corrosion rate testing was conducted using the Linear Polarization Resistance (LPR) method in accordance with ASTM G59 standards. The parameters analyzed included mass loss, polarization resistance, and corrosion rate in mm/year. The results showed that variations in plating time affect the coating thickness and corrosion rate of ST37 steel. The coating with a plating time of 35 minutes produced the lowest corrosion rate of 0.0099 mm/year, indicating higher corrosion resistance compared to the 25- and 45-minute variations. The 25-minute plating provided moderate protection, while the 45-minute plating showed a tendency toward increased corrosion rate due to the possible formation of micro-defects in the coating.